Role of D-Mannose in the Prevention of Recurrent Uncomplicated Cystitis: State of the Art and Future Perspectives - De Nunzio, Cosimo (Antibiotics (Basel), 2021)
Background: Urinary tract infections (UTI) are highly frequent in women, with a significant impact on healthcare resources. Although antibiotics still represent the standard treatment to manage recurrent UTI (rUTI), D-mannose, an inert monosaccharide that is metabolized and excreted in urine and acts by inhibiting bacterial adhesion to the urothelium, represents a promising nonantibiotic prevention strategy. The aim of this narrative review is to critically analyze clinical studies reporting data concerning the efficacy and safety of D-mannose in the management of rUTIs. Methods: A non-systematic literature search, using the Pubmed, EMBASE, Scopus, Web of science, Cochrane Central Register of Controlled Trials, and Cochrane Central Database of Systematic Reviews databases, was performed for relevant articles published between January 2010 and January 2021. The following Medical Subjects Heading were used: “female/woman”, “urinary tract infection”, and “D-mannose”. Only clinical studies, systematic reviews, and meta-analyses reporting efficacy or safety data on D-mannose versus placebo or other competitors were selected for the present review. Evidence was limited to human data. The selected studies were organized in two categories according to the presence or not of a competitor to D-mannose. Results: After exclusion of non-pertinent studies/articles, 13 studies were analyzed. In detail, six were randomized controlled trials (RCTs), one a randomized cross-over trial, five prospective cohort studies, and one a retrospective analysis. Seven studies compared D-mannose to placebo or others drugs/dietary supplements. Six studies evaluated the efficacy of D-mannose comparing follow-up data with the baseline. D-mannose is well tolerated, with few reported adverse events (diarrhea was reported in about 8% of patients receiving 2 g of D-mannose for at least 6 months). Most of the studies also showed D-mannose can play a role in the prevention or rUTI or urodynamics-associated UTI and can overlap antibiotic treatments in some cases. The possibility to combine D-mannose with polyphenols or Lactobacillus seems another important option for UTI prophylaxis. However, the quality of the collected studies was very low, generating, consequently, a weak grade of recommendations as suggested by international guidelines. Data on D-mannose dose, frequency, and duration of treatment are still lacking. Conclusion: D-mannose alone or in combination with several dietary supplements or Lactobacillus has a potential role in the non antimicrobial prophylaxis or recurrent UTI in women. Despite its frequent prescription in real-life practice, we believe that further well-designed studies are urgently needed to definitively support the role of D-mannose in the management of recurrent UTIs in women.